Validation of Prostate Imaging Reporting and Data System Version 2 for the Detection of Prostate Cancer - Hofbauer, Sebastian L.; Maxeiner, Andreas; Kittner, Beatrice; Heckmann, Robin; Reimann, Maximillian; Wiemer, Laura; Asbach, Patrick; Haas, Matthias; Penzkofer, Tobias; Stephan, Carsten; Friedersdorff, Frank; Fuller, Florian; et al. (The Journal of urology, 2018)
The second version of the PI-RADS™ (Prostate Imaging Reporting and Data System) was introduced in 2015 to standardize the interpretation and reporting of prostate multiparametric magnetic resonance imaging. Recently low cancer detection rates were reported for PI-RADS version 2 category 4 lesions. Therefore the aim of the study was to evaluate the cancer detection rate of PI-RADS version 2 in a large prospective cohort. The study included 704 consecutive men with primary or prior negative biopsies who underwent magnetic resonance imaging/ultrasound fusion guided targeted biopsy and 10-core systematic prostate biopsy between September 2015 and May 2017. All lesions were rated according to PI-RADS version 2 and lesions with PI-RADS version 2 category 3 or greater were biopsied. An ISUP (International Society of Urological Pathology) score of 2 or greater (ie Gleason 3 + 4 or greater) was defined as clinically significant prostate cancer. The overall cancer detection rate of PI-RADS version 2 categories 3, 4 and 5 was 39%, 72% and 91% for all prostate cancer, and 23%, 49% and 77% for all clinically significant prostate cancer, respectively. If only targeted biopsy had been performed, 59 clinically significant tumors (16%) would have been missed. The PI-RADS version 2 score was significantly associated with the presence of prostate cancer (p <0.001), the presence of clinically significant prostate cancer (p <0.001) and the ISUP grade (p <0.001). PI-RADS version 2 is significantly associated with the presence of clinically significant prostate cancer. The cancer detection rate of PI-RADS version 2 category 4 lesions was considerably higher than previously reported. When performing targeted biopsy, the combination with systematic biopsy still provides the highest detection of clinically significant prostate cancer.